Vivencia de la enfermera respecto a la muerte del paciente en el Servicio de Cirugía de mujeres del Hospital Belén de Trujillo - Aguilar Espinoza, Yesenia Amalia (2009)
The present study of qualitative type, it divided from the question from how the nurse experience the death oh his patients, which was developed using the boarding phenomenologic in the perspective of Martin Heidegger (2000). The objective of this in investigation was to analyze sympathetically the experiences of the nurses with regard to the death of the patients in the service of women’s surgery of the Hospital Belén of Trujillo. The subjects of investigation were nine nurses selected according to the experience and permanency in the service of women’s surgery. The interpretative analysis allowed the nurse the construction of nine units of meaning, unveiling to the nurse in one ex-sistiendo in the dimention of distress towards the dimention of the death. The relatives of the patients who died in the service, consider the nurse to be a family and identify her as such since he shared with them many of the events of life which they happened, unveiling besides the professional competition, the dimension humanizes.